MENUJU KESEJAHTERAAN HIDUP IKHTIAR MEMAHAMI KHILAFAH ISLAMIYAH DAN TEO-DEMOKRASI - Hidayatus Sholihah; Mumtazah Kamilah (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2017)
Islamic fundamentaly and islamic moderat communities be possessed one of types idealism who are hardfought as respons toward democratic system in effect for the moment. This written is spesific to consern discussed about khilafah islamiyah concept from HTI and democratic-Teo as well as Islamic moderat communities to bring description about compability with purpose from a communities. This written also explicit about concept on the almight souvereignty who are fondation precedent islamic fundamentaly in concept khilafah islamiyah as well as rule by the people souvereignty democracy to the find point source two of them.